(untitled) (IIUC Business Review, 2022)
Capital flight from Turkey throughout the last few decades is one of the major policy concerns for the development prospects of the economy. Several studies address the issue of capital flight from Turkey, but there is no significant study that examines its impact on the economic growth of the economy. The study investigates the effect of capital flight from Turkey on its economic growth during 1981-2019. It measures the extent of capital flight from Turkey adopting the World Bank’s residual method and examines its growth effect in a setting of Barro’s growth model. The study employs the Johansen cointegration approach to determine whether there exists an association between flight capital and the output growth of Turkey in the long run. The study results support the view that the flight of capital from Turkey deteriorates the country’s output growth in the long run. It implies that the government should adopt policies to reduce capital flight, increase domestic investment, and stimulate economic growth. IIUC Business Review Vol. 9, Dec. 2020 pp. 9-26